2022
DOI: 10.1111/jocn.16406
|View full text |Cite
|
Sign up to set email alerts
|

Use of physical restraints and its associated risk factors in the aged care facilities: A multicentre cross‐sectional study

Abstract: Aims and Objectives To investigate the use of physical restraints in aged care facilities(ACFs)and analyse its associated risk factors. Background Physical restraints have been widely used in ACFs worldwide, but they can cause physical and mental harm to older people. It is important to regulate the use of physical restraint. Design A cross‐sectional observational and correlational multicentre study. Methods By convenience sampling method, we selected eight ACFs in four representative regions of Hunan province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have identified that the risk factors of PR use are associated with (1) individual-related factors (eg, age, cognitive impairment, mobility decline, care dependency, fall risk, etc) [ 16 - 18 ], (2) facility-related factors (eg, facility type, ownership, and staff levels) [ 6 , 17 , 19 ], and (3) caregiver-related factors (eg, knowledge, attitude, and intention) [ 20 - 22 ]. Nevertheless, the interaction between these predictors and their clinical value remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified that the risk factors of PR use are associated with (1) individual-related factors (eg, age, cognitive impairment, mobility decline, care dependency, fall risk, etc) [ 16 - 18 ], (2) facility-related factors (eg, facility type, ownership, and staff levels) [ 6 , 17 , 19 ], and (3) caregiver-related factors (eg, knowledge, attitude, and intention) [ 20 - 22 ]. Nevertheless, the interaction between these predictors and their clinical value remains unclear.…”
Section: Introductionmentioning
confidence: 99%